Land constraints and agricultural intensification in Ethiopia: A village-level analysis of high-potential areas - Headey, Derek D.; Dereje, Mekdim; Ricker-Gilbert, Jacob; Josephson, Anna; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2013)
Highland Ethiopia is one of the most densely populated regions of Africa and has long been associated with both Malthusian disasters and Boserupian agricultural intensification. This paper explores the race between these two countervailing forces, with the goal of informing two important policy questions. First, how do rural Ethiopians adapt to land constraints? And second, do land constraints significantly influence welfare outcomes in rural Ethiopia?